Characterization of fracture properties of thin aluminum inclusions embedded in anisotropic laminate composites - Gabriella Bolzon; Vladimir Buljak; Emanuele Zappa (Fracture and Structural Integrity)
The fracture properties of thin aluminum inclusions embedded in anisotropic paperboard composites, of interest for food and beverage packaging industry, can be determined by performing tensile tests on non-conventional heterogeneous specimens. The region of interest of the investigated material samples is monitored all along the experiment by digital image correlation techniques, which allow to recover qualitative and quantitative information about the metal deformation and about the evolution of the damaging processes leading to the detachment of the inclusion from the surrounding laminate composite. The interpretation of the laboratory results is supported by the numerical simulation of the tests.